2016
DOI: 10.4338/aci-2015-12-ra-0169
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Decision Support Tool for Parental Tobacco Treatment in Hospitalized Children

Abstract: SummaryObjectives: To create and evaluate the feasibility, acceptability, and usability of a clinical decision support (CDS) tool within the electronic health record (EHR) to help pediatricians provide smoking cessation counseling and treatment to parents of hospitalized children exposed to secondhand smoke (SHS). Methods: Mixed method study of first-year pediatric residents on one inpatient unit. Residents received training in smoking cessation counseling, nicotine replacement therapy (NRT) prescribing, and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…37,38 Promising research suggests that the use of clinical decision support systems within the electronic health record may help to facilitate the systematic screening and counseling of all caregivers who smoke by healthcare providers in the ED and other settings. 3943 As healthcare providers find clinical decision support system use both feasible and acceptable, further research is needed to determine how the routine use of these tools impacts future SHSe-related morbidity, visits, and costs in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Promising research suggests that the use of clinical decision support systems within the electronic health record may help to facilitate the systematic screening and counseling of all caregivers who smoke by healthcare providers in the ED and other settings. 3943 As healthcare providers find clinical decision support system use both feasible and acceptable, further research is needed to determine how the routine use of these tools impacts future SHSe-related morbidity, visits, and costs in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Noninterruptive CDS tools, which do not require stoppage of other electronic health record (EHR) activity, may be less subject to alert fatigue [6,7]. A number of studies have demonstrated that noninterruptive alerts can increase provider compliance with care measures such as venous thromboembolism prevention in the inpatient setting [8,9], yet this type of alert is generally perceived as less successful at changing provider behavior compared with interruptive alerts [6,7]. Nonetheless, the few studies that compare the relative uptake of interruptive and noninterruptive alerts have not consistently shown interruptive alerts to be superior [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, despite assumptions that noninterruptive alerts have less effect on workflow [6,7], there has been little evaluation of the relative usability of interruptive and noninterruptive alerts. Although prior studies have evaluated the usability of either interruptive or noninterruptive alerts [9,12,13], we are unaware of studies that have compared the usability of these 2 implementation approaches. Information about their relative usability can help inform developers of CDS about the relative advantages of interruptive and noninterruptive alerts.…”
Section: Introductionmentioning
confidence: 99%
“…This study adds to the growing literature supporting the use of CDSS to increase standardized TSE screening and interventions in the pediatric healthcare setting. 3941 This model has the potential to improve the delivery and outcomes of evidence-based TSE screening and treatment in the UC setting. The use of the CDSS resulted in the identification of large numbers of children who were exposed to tobacco smoke and there were increases in the proportion of caregivers who were advised to quit and assessed for readiness to quit.…”
Section: Discussionmentioning
confidence: 99%